Oxygen, iron, carbon, and superoxide control of the fumarase fumA and fumC genes of Escherichia coli: role of the arcA, fnr, and soxR gene products. - Park, S J (1995)
The tricarboxylic acid cycle enzyme fumarase catalyzes the interconversion of fumarate to L-malate. Escherichia coli contains three biochemically distinct fumarases. While the fumA and fumB genes encode heat-labile, iron-containing fumarases, the fumC gene product is a heat-stable fumarase which does not require iron for activity. To study how the fumA and fumC genes are regulated, we constructed lacZ operon fusions to the fumA and/or fumC upstream regions. Expression of the fumA and fumC genes was lowest during anaerobic cell growth, in support of the proposed roles of FumA and FumC as aerobic fumarases. Transcription of the fumC gene was shown to be complex: it was dependent on both the fumA and fumC promoters. Anaerobic expression from the fumA promoter was derepressed in both an arcA and a fnr mutant, while expression from the fumC promoter was derepressed in only the arcA strain. The fumA promoter was also shown to be catabolite controlled, whereas the fumC promoter was relatively unaffected by the type of carbon used for cell growth. Cellular iron limitation stimulated fumC but not fumA expression. Superoxide radicals also caused increased fumC gene expression; fumA expression was unaffected. Both the superoxide control and the iron control of fumC expression required the SoxR regulatory protein. These studies suggest different physiological roles for the FumA and FumC fumarases. The iron-containing FumA fumarase is the more abundant enzyme under most conditions of aerobic cell growth except when iron is limiting; FumC, which lacks iron, appears to be a backup enzyme that is synthesized optimally only when iron is low or when superoxide radicals accumulate.